THE EFFECT OF TIME DEACETYLATION TO CHARACTERIZE CHITOSAN FROM WASTE SHRIMP - Marni Kaimudin; Mozes Radiena (Pattimura University, 2017)
This research aims to look at the effect of time deacetylation of the chitosan characterization of the results of the utilization of waste shrimp. The method was used in this research is an experimental method to the treatment of different deacetylation time. Observation results include moisture, ash, fat and protein are shown in figures and tables. The content of chitosan in the shells of 40.35% to the deacetylation for 3 hours, 37.27% to deacetylation for 4 hours and 33.15% to the deacetylation for 5 hours. The characterization results obtained are water content of 75.10% for shrimp waste, 15.26% to chitosan with deacetylation for 3 hours, 10.15% to deacetylation for 4 hours and 9.66% for the deacetylation for 5 hours, ash content of 5.02% for shrimp waste, 3.18% of chitosan by deacetylation for 3 hours, 1.14% to deacetylation for 4 hours and 0.10% to deacetylation for 5 hours. At 2.47% fat content for shrimp waste, 2.02% for chitosan with deacetylation for 3 hours, 1.71% for deacetylation for 4 hours and 0.29% to deacetylation for 5 hours. The protein content of 14.85% for shrimp waste, 3.34% for chitosan with deacetylation for 3 hours, 1.93% for deacetylation for 4 hours and 0.69% for the deacetylation for 5 hours. The characterization results that meet the protant laboratory standard Inc. chitosan is ash, fat and protein, while the water content does not meet the standards. Degree of deacetylation of 83.25% on deacetylation for 5 hours. Chitosan typical uptake seen in the results of chemical tests FTIR with wavenumbers 1,666.50 cm-1. The effect of time deacetylation of the chitosan are very significant characterization in accordance with the test results analysis of variance.